Taxonomy of Pseudopimpla Habermehl (Hymenoptera: Ichneumonidae: Pimplinae) with description of a new species - Mazón, Marina; Bordera, Santiago (Zootaxa, 2010)
Pseudopimpla propodeumpunctata sp. nov., collected in Spain, is described. Differences and similarities between both West-Palaearctic species, P. algerica and P. pygidiator, were checked by mean of morphometric survey and multivariate analysis. The morphometric results showed no differences between both species, and as a consequence they were synonymized. A key for the world species of Pseudopimpla is provided. A new host, Hartigia nigra (Harris) (Hymenoptera, Cephidae) and two new host food plants (Rosa sp and Rubus ulmifolius Schott) are reported for P. algerica. Pseudopimpla is recorded for the first time from the Iberian Peninsula and Serbia.